2006
DOI: 10.1017/s0031182006001302
|View full text |Cite
|
Sign up to set email alerts
|

Anthelmintic action of plant cysteine proteinases against the rodent stomach nematode,Protospirura muricola,in vitroandin vivo

Abstract: A note on versions:The version presented here may differ from the published version or from the version of record. If you wish to cite this item you are advised to consult the publisher's version. Please see the repository url above for details on accessing the published version and note that access may require a subscription. Cysteine proteinases from the fruit and latex of plants, including papaya, pineapple and fig, were previously shown to have a rapid detrimental effect, in vitro, against the rodent gastr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
49
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 44 publications
(61 reference statements)
9
49
1
Order By: Relevance
“…Cysteine proteinases isolated from different fruits were shown to cause wrinkles and folds of the cuticle, often followed by blistering and gradual digestion of the cuticle on different nematodes (Stepek et al, 2005(Stepek et al, , 2006(Stepek et al, , 2007. Thus, structural alterations observed on A. galli cuticle in the present study were definitely due to the anthelmintic activity of the extract of A. oxyphylla stem bark.…”
Section: Discussionsupporting
confidence: 49%
“…Cysteine proteinases isolated from different fruits were shown to cause wrinkles and folds of the cuticle, often followed by blistering and gradual digestion of the cuticle on different nematodes (Stepek et al, 2005(Stepek et al, , 2006(Stepek et al, , 2007. Thus, structural alterations observed on A. galli cuticle in the present study were definitely due to the anthelmintic activity of the extract of A. oxyphylla stem bark.…”
Section: Discussionsupporting
confidence: 49%
“…This effect was similar to that described previously for A. suum (Robbins, 1930;Berger & Asenjo, 1939), H. polygyrus (Stepek et al, 2005), T. muris (Stepek et al, 2006) and P. muricola (Stepek et al, 2007a), indicating that plant cysteine proteinases have a broad spectrum of activity against parasitic helminths in vitro.…”
Section: Discussionsupporting
confidence: 89%
“…However, to our knowledge, the current study is the first (i) to establish, unequivocally, that it is upon the cysteine proteinases present in the latex that the anthelmintic efficacy of papaya latex depends, and (ii) to provide evidence that the mechanisms of action in vivo and in vitro are essentially indistinguishable. In vitro studies (Stepek et al 2005(Stepek et al , 2006(Stepek et al , 2007 have demonstrated that cysteine proteinases attack the protective cuticle of the nematode, rapidly leading to complete dissolution of the parasite, a mechanism of action that differs from all the current anthelmintic drugs (Sangster and Gill, 1999 ;Martin and Robertson, 2000). This effect was similar to that described previously for 3 other gastrointestinal nematodes, H. polygyrus (Stepek et al 2005), T. muris (Stepek et al 2006) and Ascaris suum (Robbins, 1930 ;Berger and Asenjo, 1939), indicating that plant cysteine proteinases have a broad spectrum of activity against GI nematodes in vitro.…”
Section: Discussionmentioning
confidence: 99%